Pilot Trial of a Home-based Physical Activity Program for African American Women. Issue 12 (December 2017) - PEKMEZI, DORI; AINSWORTH, COLE; JOSEPH, RODNEY P.; WILLIAMS, VICTORIA; DESMOND, RENEE; MENESES, KAREN; MARCUS, BESS; DEMARK-WAHNEFRIED, WENDY
ABSTRACT: Purpose: This study aimed to assess the feasibility of a Home-based, Individually-tailored Physical activity Print (HIPP) intervention for African American women in the Deep South. Methods: A pilot randomized trial of the HIPP intervention ( N = 43) versus wellness contact control ( N = 41) was conducted. Recruitment, retention, and adherence were examined, along with physical activity (7-d physical activity recalls, accelerometers) and related psychosocial variables at baseline and 6 months. Results: The sample included 84 overweight/obese African American women 50–69 yr old in Birmingham, AL. Retention was high at 6 months (90%). Most participants reported being satisfied with the HIPP program and finding it helpful (91.67%). There were no significant between-group differences in physical activity ( P = 0.22); however, HIPP participants reported larger increases (mean of +73.9 min·wk −1 (SD 90.9)) in moderate-intensity or greater physical activity from baseline to 6 months compared with the control group (+41.5 min·wk −1 (64.4)). The HIPP group also reported significantly greater improvements in physical activity goal setting ( P = 0.02) and enjoyment ( P = 0.04) from baseline to 6 months compared with the control group. There were no other significant between-group differences (6-min walk test, weight, physical activity planning, behavioral processes, stage of change); however, trends in the data for cognitive processes, self-efficacy, outcome expectations, and family support for physical activity indicated small improvements for HIPP participants ( P > 0.05) and declines for control participants. Significant decreases in decisional balance ( P = 0.01) and friend support ( P = 0.03) from baseline to 6 months were observed in the control arm and not the intervention arm. Conclusions: The HIPP intervention has great potential as a low-cost, high-reach method for reducing physical activity–related health disparities. The lack of improvement in some domains may indicate that additional resources are needed to help this target population reach national guidelines.